A Comparison of Digital Constant On-Time and Variable On-Time Control in Buck/Buck-Boost PFC Converter - Zafer ORTATEPE (Gazi Üniversitesi Fen Bilimleri Dergisi, 2023)
This study compares two frequently used control strategies in the context of completely digitally controlled critical conduction mode (CRM) buck/buck-boost converters, namely constant on-time (COT) and variable on-time (VOT). The aim of this research is to compare and assess the performance of different control systems in terms of power factor (PF) and total harmonic distortion (THD). The COT control technique employs a fixed on-time period for each switching cycle, resulting in a predictable and straightforward control scheme. On the other hand, VOT control dynamically adapts the on-time period based on the input and output voltage conditions, offering potential advantages in terms of load regulation and stability. The analysis results provide valuable insights into the strengths and limitations of each control technique. Additionally, the dynamic behavior of the converters under various operating conditions is investigated, shedding light on the stability and robustness aspects of each control scheme. The study is conducted using a fully digital setup and evaluated in Matlab/Simulink environment. The findings show that VOT control outperforms COT in terms of THD and PF under steady-state conditions. These findings offer valuable guidance for selecting the appropriate control technique for PFC converters, depending on specific requirements of their applications.